Public sector accounting - BUDDING, T.; GROSSI, G.; TAGESSON, T. (Routledge, 2015)
As change sweeps across the public sector, a huge range of accounting and financial management challenges are created. This textbook analyses the reforms that are being introduced to deal with these challenges and their global impact on the public sector. Readers are provided with an international overview of government accounting, reporting, management control, cost accounting, budgeting and auditing. In explaining how innovative financial management tools are utilized in the public sector, the authors address a number of emerging issues:Harmonization trends